Coal gangue-based grouting material and preparation method thereof
By developing coal gangue-based grouting materials and replacing traditional cement with coal gangue, the problems of high energy consumption of cement and low utilization rate of coal gangue are solved, and resource utilization and environmentally friendly engineering materials are achieved.
Patent Information
- Application Number
- CN202510082076.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional cement, as a high-energy-consuming industrial product, has led to high global resource consumption, and coal gangue, as solid waste in coal mining, has low utilization rate, and poses safety risks and ecological and environmental pollution problems.
Develop a coal gangue-based grouting material whose components include coal gangue, exciter, fiber material, mineral additive and water, which is prepared by pretreatment, addition of modifiers and mixing, and replaces traditional cement.
The resource utilization of solid waste has been achieved, the use of traditional cement has been significantly reduced, high energy consumption and environmental pollution have been reduced, and the material performance is close to that of traditional cement.
Smart Images

Figure CN119822703A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of building materials, and specifically relates to a gangue-based grouting material and a preparation method thereof. Background Art
[0002] As the main solid waste in the process of coal mining and washing, coal gangue has the characteristics of large output and low utilization rate. Large-scale accumulation not only occupies land resources, but also brings serious safety risks and ecological environmental pollution problems. Due to its stable physical and chemical properties in its natural state, coal gangue faces multiple limitations in terms of quality, activity and cost in terms of resource utilization, so it is urgent to develop green and efficient disposal and utilization technologies. Traditional grouting materials have a high cement content, and cement, as a high-energy-consuming industrial product, consumes a lot of global resources, so it is urgent to find an alternative cementitious material with lower energy consumption. Summary of the invention
[0003] In view of the deficiencies in the prior art, the purpose of the present application is to provide a gangue-based grouting material and a preparation method thereof. The grouting material prepared in the present application can replace traditional cement, thereby reducing high energy consumption and environmental pollution.
[0004] To achieve the above objectives, this application provides the following technical solutions:
[0005] A gangue-based grouting material, the composition of the grouting material and the mass percentage of each component are: gangue: 40wt% to 70wt%; activator: 3wt% to 10wt%; fiber material: 0.5wt% to 5wt%; mineral additive: 10wt% to 30wt%; water: balance.
[0006] The present application also provides a method for preparing a coal gangue-based grouting material, the method comprising: pretreating coal gangue to obtain a coal gangue-based grouting material precursor; adding a modifier to the coal gangue-based grouting material precursor; mixing and stirring the coal gangue-based grouting material precursor containing the modifier with a mineral additive to obtain a dry mix; and mixing the dry mix with water to obtain a coal gangue-based grouting material.
[0007] Optionally, the pretreatment of the coal gangue includes: drying the coal gangue; screening and crushing the dried coal gangue to obtain fine coal gangue powder; and thermally activating the fine coal gangue powder to obtain a coal gangue-based grouting material precursor.
[0008] Optionally, the gangue is dried by gradually increasing the temperature.
[0009] Optionally, the screened coal gangue is crushed by graded crushing.
[0010] Optionally, the coal gangue fine powder is thermally activated by supercritical water oxidation activation.
[0011] Optionally, the modifier includes an activator and a fiber material.
[0012] Optionally, the activator includes any one of the following: an alkaline activator, a sulfate activator, an aluminate activator and an organic activator.
[0013] Optionally, the fiber material includes synthetic fiber material or natural fiber material.
[0014] Optionally, the ratio of the dry mix to water is 0.35 to 0.45.
[0015] Compared with the prior art, the beneficial effects brought by the present application are as follows: the present application realizes the effective resource utilization of solid waste by developing a coal gangue-based grouting material, significantly reduces the use of traditional cement, and thus reduces high energy consumption and environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is a schematic flow chart of a method for preparing a gangue-based grouting material provided in one embodiment of the present application. DETAILED DESCRIPTION
[0017] The specific embodiments of the present application will be described in detail below with reference to the accompanying drawings. Although the specific embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.
[0018] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the implementation of the present application, but the description is based on the general principles of the specification and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.
[0019] To facilitate understanding of the embodiments of the present application, further explanation will be given below using specific embodiments as examples in conjunction with the accompanying drawings, and the various drawings do not constitute a limitation on the embodiments of the present application.
[0020] In an exemplary embodiment, the present application provides a gangue-based grouting material, the components of the grouting material and the mass percentage of each component are: gangue: 40wt% to 70wt%; activator: 3wt% to 10wt%; fiber material: 0.5wt% to 5wt%; mineral additives: 10wt% to 30wt%; water: the balance.
[0021] In this embodiment, the ratio of the above components is obtained by the present application through a series of theoretical analysis and experimental verification, wherein the coal gangue is the main component, providing the basic structure and volcanic ash activity. A higher content of coal gangue can maximize the use of this waste, reduce dependence on traditional cement, reduce production costs, and contribute to environmental protection. However, too high a proportion of coal gangue can lead to problems of poor fluidity or insufficient strength, so its proportion is set within the above range according to experimental verification.
[0022] The function of the activator is to improve the early strength and the ability to develop later strength, and activate the active components of the volcanic ash in the coal gangue. It has been proven that the activator in the above proportion can significantly improve the hardening speed and final strength of the grouting material without increasing the cost.
[0023] Fiber materials are used to enhance the tensile strength and toughness of grouting materials, prevent cracks, and help grouting materials form an internal network structure. The above proportion of fibers can improve the overall stability and durability of grouting materials, while excessive amounts will affect the fluidity of grouting materials or cause agglomeration problems.
[0024] Mineral additives are used to supplement and optimize the physical and chemical properties of gangue-based materials, such as increasing density, reducing porosity and enhancing long-term stability. The above proportions of mineral additives can also adjust the pH value and promote pozzolanic reactions.
[0025] Further, after experimental verification, the present application gives an optimal ratio, namely, fine powder of coal gangue: 55wt%, activator: 7wt%, fiber material: 2wt%, mineral additive: 20wt%, water: balance. Among them, the 55wt% coal gangue content can provide sufficient basic structure and filling capacity while ensuring good volcanic ash activity. This ratio can fully utilize waste resources without affecting the overall performance of the material due to excessively high coal gangue ratio. The 7wt% activator content is sufficient to activate the active components in the coal gangue, improve the early strength and promote the development of later strength. In addition, this ratio can also effectively avoid the cost increase or material property change caused by excessive activators. 2wt% of fiber material can significantly enhance the tensile strength and toughness of the grouting material, reduce the risk of crack formation, and help to form a stable internal network structure, and this ratio will not affect the fluidity and provide good crack resistance. 20wt% of mineral additives can optimize the physical and chemical properties of the grouting material, such as increasing density, reducing porosity, and enhancing long-term stability.
[0026] Figure 1 FIG. 1 is a flow chart of a method for preparing a gangue-based grouting material provided by an exemplary embodiment of the present application. Figure 1 As shown, the preparation method comprises the following steps:
[0027] S100: pre-treating the coal gangue to obtain a coal gangue-based grouting material precursor;
[0028] The pretreatment of coal gangue specifically includes the following steps:
[0029] S101: placing the coal gangue in a rotary dryer for drying;
[0030] In this step, spiral blades are provided inside the rotary dryer, which can continuously turn the material during rotation, thereby ensuring that the hot air is in full contact with the coal gangue.
[0031] In addition, the present application adopts a gradually increasing temperature method to dry the coal gangue, that is, it is dried at a lower temperature (e.g., 80°C) at the beginning, and then increased to a higher temperature (e.g., 120°C) as the moisture content gradually decreases. This can avoid the problem of the surface of the coal gangue drying quickly while the inside is still wet.
[0032] S102: screening and crushing the dried coal gangue to obtain coal gangue fine powder;
[0033] In this step, the dried gangue is first screened to remove large impurities and non-gangue components. Then, the screened gangue is crushed. Regarding crushing, this application introduces an innovative crushing process to obtain gangue with a more uniform particle size. Specifically, the crushing process introduced in this application includes the following stages:
[0034] Stage 1: Primary crushing of the screened gangue: The screened gangue is sent to a jaw crusher or a gyratory crusher for primary crushing, so that the gangue reaches a moderate size (for example, less than 50 mm) so that it can enter the next stage of crushing.
[0035] Stage 2: Fine crushing of the coal gangue after the initial crushing: Establish a closed-loop circulation system including hammer crusher, impact crusher and fine crusher. Each crusher is equipped with precise screening equipment to only allow coal gangue within a specific particle size range to pass through, while coal gangue with larger particle sizes is sent back to the corresponding crusher for further crushing.
[0036] Stage 3: Ultrafine crushing of finely crushed gangue: Use a high-pressure micro-powder mill (also known as a Raymond mill) to ultrafinely crush the gangue. This equipment can produce very fine and uniformly sized powder with low energy consumption, and can usually control the particle size below 0.075 mm.
[0037] By adopting the crushing process of graded crushing, the particle size distribution of each batch of coal gangue can be made more consistent. A more uniform particle size distribution helps to improve the rheology, setting time, compressive strength and other mechanical properties of the grouting material, which can not only improve the construction efficiency, but also enhance the safety and durability of the engineering structure. In addition, staged crushing can also activate the inherent volcanic ash activity of coal gangue to improve the bonding force and reactivity of coal gangue as a grouting material.
[0038] S103: thermally activating the coal gangue fine powder to obtain a coal gangue-based grouting material precursor.
[0039] In this step, the present application adopts a supercritical water oxidation activation method to perform thermal activation treatment on the coal gangue fine powder, and the method specifically includes:
[0040] First, an autoclave made of stainless steel or special alloy that can withstand high pressure and high temperature conditions is selected as a reaction vessel, and the gangue fine powder, oxidant (such as oxygen or hydrogen peroxide) and water are sent into the autoclave that has been preheated and reaches the set conditions (temperature of 400°C to 600°C, pressure of 25MPa to 40MPa). In the autoclave, as the temperature rises, the water will gradually change to a supercritical state, that is, supercritical water, and begin to exert its solvent properties. In supercritical water, organic matter can be efficiently oxidized and degraded into carbon dioxide, water and other simple small molecule compounds. At the same time, some mineral components in the gangue fine powder will also undergo phase change or structural reorganization, thereby activating the activity of volcanic ash. In addition, in supercritical water, sulfides and other harmful impurities in the gangue fine powder can be effectively removed, thereby improving the overall quality of the gangue. After the reaction is completed, the reaction product is immediately discharged from the autoclave and quickly cooled. Subsequently, the solid product, that is, the activated gangue-based grouting material precursor, is recovered by filtration, centrifugation, etc.
[0041] It should be noted that the silicates and other mineral components in the coal gangue that have not been thermally activated have low activity and cannot fully participate in the volcanic ash reaction (i.e., secondary reaction with the hydration product), which will directly lead to poor bonding properties of the coal gangue and difficulty in forming a solid hardened body. In addition, the fine powder of coal gangue that has not been thermally activated has a larger particle size distribution and a lower specific surface area, which will affect the fluidity and construction operation of the slurry, making it difficult for the slurry to fill small gaps during the subsequent injection process. Furthermore, the interaction between the particles in the unactivated fine powder of coal gangue is weak, and it is easy to separate or settle when standing, which will further affect the consistency and stability of the final grouting material.
[0042] It should also be noted that under supercritical conditions, water has excellent solubility and diffusion properties, and can quickly penetrate into the internal structure of coal gangue fine powder, so that organic matter and other impurities in the coal gangue fine powder can be almost completely converted into harmless small molecules such as carbon dioxide and water, thereby purifying the coal gangue more thoroughly. In contrast, due to the slow heat transfer of traditional heating methods, the chemical reaction rate is slow, resulting in limited purification effect of coal gangue. In addition, under supercritical conditions, some mineral components in coal gangue fine powder will undergo phase change or structural reorganization, generating more active sites, which will help improve the adhesion and reactivity of coal gangue as a grouting material. Ordinary heating activation can usually only activate certain active ingredients through simple thermal effects, and the activation effect is limited.
[0043] S200: adding a modifier to the gangue-based grouting material precursor;
[0044] In this step, first, an appropriate amount of alkaline activator (such as sodium hydroxide, potassium hydroxide and sodium silicate) or other types of activators (such as sulfate activators (such as gypsum and sodium sulfate), aluminate activators (such as aluminum powder), organic activators (such as lignin sulfonate)) is added to the coal gangue-based grouting material precursor. The main function of the activator is to improve its early strength and ability to develop later strength by chemically reacting with the active components in the coal gangue.
[0045] It should be noted that the activator needs to be evenly distributed throughout the gangue-based grouting material precursor to ensure that all particles can be activated. In order to ensure that the activator is evenly distributed in the gangue-based grouting material precursor, the following operations can be referred to: first pre-mix the activator with a small amount of gangue-based grouting material precursor (for example, 10% of the total amount) to form a "masterbatch", and then mix the masterbatch with the remaining gangue powder. This method can significantly improve the initial dispersibility of the activator. Then, the masterbatch and the remaining gangue-based grouting material precursor are placed in a double-helix conical mixer. This mixer can achieve continuous circulation of materials from bottom to top through the relative rotation of two spiral blades, thereby ensuring that the activator and the gangue-based grouting material precursor are fully mixed. After the mixing is completed, a vibrating screen is needed to remove the large particles that may remain or the incompletely mixed parts, so as to ensure the uniform distribution of the final activator in the gangue-based grouting material precursor.
[0046] Secondly, adding synthetic fibers (such as polypropylene fibers) or natural fibers (such as wood fibers) to the gangue-based grouting material precursor containing the activator can affect the chemical reaction environment between the activator and the gangue-based grouting material precursor, especially when the fiber surface contains certain active functional groups. Second, the role of the fiber is to form a network structure inside the gangue-based grouting material precursor, thereby improving the tensile strength and toughness of the gangue-based grouting material precursor.
[0047] It should be noted that the activator and the fiber material need to be added in a sequential order because: since the activator needs to be evenly distributed throughout the gangue-based grouting material precursor to ensure that all particles can be activated, if the fiber is added first, it will hinder the uniform dispersion of the activator, thereby affecting the final effect. In addition, the formation of a network structure of the fiber inside the gangue-based grouting material precursor depends on the uniform distribution of the fiber in the gangue-based grouting material precursor. If the fiber is added before the activator reaction is completed, the uniformity and reaction efficiency of the activator will be affected due to operations such as stirring.
[0048] S300: mixing and stirring a coal gangue-based grouting material precursor containing a modifier and a mineral additive to obtain a dry mix;
[0049] In this step, first, the gangue-based grouting material precursor containing the modifier and the mineral additive (such as slag powder or silica fume) are respectively sent into the premixing bin for preliminary stirring to reduce the agglomeration of large particles and improve the dispersion efficiency of the gangue-based grouting material precursor containing the modifier and the mineral additive in the subsequent mixing process.
[0050] Secondly, the gangue-based grouting material precursor containing modifier and the mineral additive are added to the main mixer in layers, that is, the larger volume of gangue-based grouting material precursor is added first as the bottom layer, and then the mineral additive is covered on the gangue-based grouting material precursor. This layering method can prevent components such as lightweight fibers from floating on the surface, ensuring that all components can be fully contacted and mixed.
[0051] Finally, a three-dimensional motion agitator with multiple rotating axes is used to stir the mixed coal gangue-based grouting material precursor containing modifier and mineral additives. The use of a three-dimensional motion agitator can not only subject the mixed materials to shear force in the horizontal direction, but also effectively flip and toss them in the vertical direction, which helps to break up any lumps that may be formed and promote a more uniform distribution.
[0052] Through the above steps, an efficient and uniform dry mix preparation process can be achieved, ensuring the best mixing effect between the gangue-based grouting material precursor containing the modifier and the mineral additive.
[0053] S400: Mixing the dry mixture with water to obtain a gangue-based grouting material.
[0054] In this step, the optimal water-solid ratio is first found through laboratory tests. The gangue-based grouting material in this application is mainly used to replace cement. Through comprehensive analysis of factors such as fluidity and strength, this application sets the optimal water-solid ratio to between 0.35 and 0.45 (for example, 100 kg of dry mix requires 35 kg to 45 kg of water).
[0055] After determining the optimal water-solid ratio, pour the dry mix into the mixer first, then slowly add the pre-calculated amount of water to start preliminary mixing. Next, start the mixer and stir thoroughly, with the stirring time set to 3 to 5 minutes. After the stirring is completed, the gangue-based grouting material can be obtained.
[0056] In another exemplary embodiment, the present application also provides a method for preparing a gangue-based grouting material. Different from the above-mentioned embodiment, in the pretreatment stage, after ultra-fine crushing of the gangue, this embodiment further introduces an air flow crushing process, that is, air flow crushing is used to process the hard part of the gangue that is difficult to obtain an ideal particle size through mechanical crushing. Specifically, the air flow crushing process is described as follows:
[0057] First, air or other inert gases (such as nitrogen, used to prevent oxidation reactions) are compressed to high pressure using a compressor and stored in a gas tank.
[0058] Secondly, the ultra-finely crushed gangue is fed into the air flow crusher. At the same time, high-pressure gas is ejected at a very high speed through a special nozzle, mixed with the ultra-finely crushed gangue and accelerated to a high speed. The high-speed moving gangue particles collide and rub against each other under the action of the air flow, resulting in rupture and refinement. Due to the direct collision between particles, this pulverization method can produce very fine and uniform powder, and the particle size can usually be controlled at the micron level or even submicron level.
[0059] Finally, the coal gangue powder obtained after crushing is screened to ensure that the fine powder within the target particle size range is collected, while the larger particles are sent back to the air flow crushing area for further crushing until all the coal gangue reaches the required fineness.
[0060] In summary, air flow crushing can further quickly crush the ultra-finely crushed coal gangue in a short time, and because air flow crushing adopts the self-collision method between particles, it can obtain products with narrow particle size distribution and regular shape, which helps to improve the fluidity and filling performance of the grouting material.
[0061] In another exemplary embodiment, the present application also provides a method for preparing a gangue-based grouting material. Different from the above-mentioned embodiment, in the process of mixing the dry mix with water, a water reducer is used in this embodiment. At this time, the water reducer is first sprayed evenly into the mixer, and stirring is continued to ensure that the water reducer is fully mixed. It should be noted that the water reducer needs to be added in an appropriate amount, that is, 0.5 to 1 kg of water reducer can be added for every 100 kg of dry mix.
[0062] In this embodiment, by adding a water reducing agent, on the one hand, the fluidity of the slurry can be significantly increased while maintaining or reducing the amount of water, making it easier to pump the grouting material and fill the gaps in the complex structure. On the other hand, since the presence of excess water is reduced, the water reducing agent can help generate fewer pores, thereby improving the density and long-term strength of the final hardened body. On the other hand, the water reducing agent can control the speed of water evaporation, which can reduce the drying shrinkage of the grouting material to a certain extent, thereby reducing the possibility of cracks in the grouting material.
[0063] In this embodiment, the water reducer includes, for example, lignin sulfonates, naphthalene-based high-efficiency water reducers, aminosulfonates, polycarboxylic acid-based high-efficiency water reducers, aliphatic high-efficiency water reducers, and composite water reducers. After testing, this embodiment preferably uses polycarboxylic acid-based high-efficiency water reducers because: compared with other water reducers, polycarboxylic acid-based water reducers can achieve extremely high water reduction effects at extremely low dosages, up to more than 30%, which is particularly important for grouting materials that require high fluidity, and can ensure that the grouting materials can smoothly fill the gaps in complex structures. In addition, due to its efficient dispersion effect, polycarboxylic acid-based water reducers help grouting materials form a denser microstructure, thereby accelerating the development of early strength and ensuring good later strength. Furthermore, polycarboxylic acid-based water reducers can minimize the drying shrinkage of grouting materials, thereby minimizing the possibility of cracks.
[0064] In addition, the present application compares the mechanical properties, fluidity and durability of the grouting material prepared by the method described in the present application with traditional cement, as well as the environmental impact and economic benefits. The comparison results are shown in Tables 1 to 5:
[0065] Table 1 Comparison of mechanical properties
[0066]
[0067] Table 2 Liquidity comparison
[0068]
[0069] Table 3 Durability comparison
[0070]
[0071] Table 4 Comparison of environmental impact
[0072]
[0073] Table 5 Comparison of economic benefits
[0074]
[0075] Based on Tables 1 to 5, it can be seen that although the gangue-based grouting material is slightly lower than traditional cement in some absolute values (such as compressive strength and flexural strength), it has significant advantages in early strength development, fluidity, durability (especially freeze-thaw resistance and sulfate corrosion resistance), environmental friendliness and economic benefits. These characteristics make the material very suitable for application in a variety of engineering scenarios, especially in projects with high requirements for green buildings and sustainable development. Therefore, the gangue-based grouting material provided in this application can be used as an effective substitute to replace traditional cement for application in various engineering scenarios.
[0076] The above embodiments are only for illustrating the technical concept and features of the present application, and their purpose is to enable people familiar with the technology to understand the content of the present application and implement it accordingly, and they cannot be used to limit the protection scope of the present application. Any equivalent changes or modifications made according to the spirit of the present application should be included in the protection scope of the present application.
Claims
1. A gangue-based grouting material, characterized in that: The composition of the grouting material and the mass percentage of each component are: Coal gangue: 40wt%~70wt%; Activator: 3wt%~10wt%; Fiber material: 0.5wt%~5wt%; Mineral additives: 10wt% to 30wt%; Water: Balance.
2. A method for preparing a gangue-based grouting material, characterized in that: The method comprises: Pre-treating the coal gangue to obtain a coal gangue-based grouting material precursor; adding a modifier to the gangue-based grouting material precursor; The gangue-based grouting material precursor containing the modifier is mixed and stirred with a mineral additive to obtain a dry mix; The dry mixture is mixed with water to obtain a gangue-based grouting material.
3. The method for preparing a gangue-based grouting material according to claim 2, characterized in that: The pretreatment of the coal gangue comprises: Drying of coal gangue; Screening and crushing the dried coal gangue to obtain fine coal gangue powder; The coal gangue fine powder is subjected to thermal activation treatment to obtain a coal gangue-based grouting material precursor.
4. The method for preparing a gangue-based grouting material according to claim 3, characterized in that: The gangue is dried by gradually increasing the temperature.
5. The method for preparing a gangue-based grouting material according to claim 3, characterized in that: The screened coal gangue is crushed by graded crushing.
6. The method for preparing a gangue-based grouting material according to claim 3, characterized in that: The coal gangue fine powder is thermally activated by supercritical water oxidation activation.
7. The method for preparing a gangue-based grouting material according to claim 2, characterized in that: The modifying agent includes an activator and a fiber material.
8. The method for preparing a gangue-based grouting material according to claim 7, characterized in that: The activator includes any one of the following: an alkaline activator, a sulfate activator, an aluminate activator and an organic activator.
9. The method for preparing a gangue-based grouting material according to claim 7, characterized in that: The fiber material includes synthetic fiber material or natural fiber material.
10. The method for preparing a gangue-based grouting material according to claim 2, characterized in that: The ratio of the dry mix to water is 0.35 to 0.45.
Citation Information
Patent Citations
Wheat straw fiber-reinforced gangue geopolymer material and preparation method thereof
CN107500585A
Gangue-based geopolymer grouting material and preparation method thereof
CN112250366A
Method for oxidizing and activating coal gangue through subcritical / supercritical water
CN114247725A
Alkali-activated cementing material and preparation method thereof
CN118812198A